MEMAHAMI PENDEKATAN DAN HABITUASI PKn SEBAGAI PENDIDIKAN NILAI DAN MORAL BAGI GURU DI SEKOLAH DASAR - Wachid Pratomo (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Education is a conscious and planned attempt to create a learning atmosphere and a learning process in order that learners actively develop their potentials to possess spiritual and religious power, self-control, personality, intelligence, noble characters, and skills needed by themselves, the society, nation, and country. Civic Education at the elementary school requires learning through a variety of approaches emphasizing the habituation of the students by the teachers in inculcating values and moral. Therefore, the teachers are expected to prioritize the among (guiding) system and apply the values by providing examples (ing ngarso sung tulodo), developing will (ing madyo mangun karso), and enhancing the studentsâ€™ creativity in the learning process (tut wuri handayani). In this way, the students understand Civic Education as value and moral education which finally can produce students with good morals and characters for the development of the nation and country.Â